Scanning electron microscopic study of cold-stored small bowel: comparison of Euro-Collins and Lactated Ringer's solutions - ERCAN, FERİHA (My University, 2003)
The increasing use of the small bowel for transplantation necessitates the development of optimum preservation techniques. The aim of our study was to investigate time-related morphological changes of the rat small bowel during preservation of the organ in hypothermic Euro-Collins and Lactated Ringer's solutions. It is the only study comparing these widely used preservation solutions with scanning electron microscopy, which is especially suitable to show the intestinal mucosa, one of the tissues of the intestine most susceptible to ischemia. Small bowels were perfused with either Euro-Collins, Lactated Ringer's or physiological saline solution and placed in respective preservation solutions at 4 degrees C for 0, 3, 6 and 12 hours. Biopsy samples were prepared for examination at the light and scanning electron microscopic levels. According to the results of this study we conclude that, even Lactated Ringer's solution showed better tissue preservation than Euro-Collins solution, both preservation solutions are suitable for short term preservation of the small bowel and that further ameliorations of the preservation solutions and/or techniques are required for long term preservation.
Keywords: Female; Animals; Male; Rats; Sensitivity and Specificity; Rats, Wistar; Intestinal Mucosa; Probability; Microscopy, Electron; Cold Temperature; Intestine, Small; Models, Animal; Hypertonic Solutions; Organ Preservation; Organ Preservation Solutions; Isotonic Solutions; Ringer's Lactate